Exploring Synergy of Computing Power and Electricity： Unearthing Flexibility of High-Voltage Direct Current-Side Integrated Backup and Energy Storage Batteries - CHEN Min, GUO Qinglai, JING Tangbo, PAN Yu, ZHAI Sicheng, LI Zihao (Dianli jianshe)
Exploiting inherent load flexibility within data centers is key to achieving synergy between computing power and electricity. This study focuses on the idle flexibility of integrated backup and energy storage batteries on the side of high-voltage direct current （HVDC） communication power supplies in data centers. An application scenario for this idle flexibility， which enhances the supported workload of cabinets to achieve premium applications， is proposed. Meanwhile， it simultaneously provides load flexibility to the grid to obtain compensation from electricity ancillary service markets and reduce electricity costs. Specifically， this study presents the principle for this application scenario and discusses the value assessment under different scenarios， providing a theoretical foundation for determining the idle flexibility of HVDC-side integrated energy storage and backup batteries. Finally， prospects for exploring the synergy between computing power and electricity are discussed.